Analyzing the Influence of Social Media on Pro-Environmental Behavior via the Mediation of Pro-Environmental Knowledge and Attitudes among Middle School Students in Bandung Regency, Indonesia - Amriwijaya, Julian; Sunggoro Trirahardjo (HM Publisher, 2024)
Adolescents, even those in junior high school, have incorporated social media into their daily routines, making it an essential component of their lives. The objective of this study is to examine how social media influences the adoption of pro-environmental behavior among junior high school students in Bandung Regency, Indonesia, by mediating their pro-environmental knowledge and attitudes. This study employs quantitative methodologies via a survey-based approach. We administered questionnaires to a sample of 300 junior high school students in Bandung Regency to collect data. The questionnaire encompasses inquiries on social media use, pro-environmental knowledge, pro-environmental attitudes, and pro-environmental conduct. The research findings indicate that social media exerts a beneficial influence on the pro-environmental conduct of junior high school pupils. The statistically significant positive correlation coefficient (r = 0.35, p < 0.01) supports the connection between the usage of social media and pro-environmental behavior. Pro-environmental knowledge and attitudes influence the connection between social media use and pro-environmental behavior, as revealed by mediation analysis. Consequently, social media enhances students' understanding and beliefs about the environment, thereby motivating them to engage in environmentally friendly actions. The findings of this study demonstrate that social media can serve as a potent instrument for promoting pro-environmental conduct among adolescents in junior high school.